Preventive Action for Anemia with Education for Pregnant Women in Kesambe Lama Village, East Curup District - Utami, Nabila Sarli; Junanti , Yetty Novia; Setiani, Setiani; Fitriyanti , Linda; Komariyah , Siti; Putri , Yesi (Jurnal Pengabdian Mandiri, 2024)
Anemia is a condition when the number of red blood cells or the concentration of oxygen transporter Hemoglobin (Hb) in the blood is insufficient for the body's physiological needs. In pregnancy, the need for oxygen is higher, triggering an increase in entropoietin production. As a result, plasma volume increases and red blood cells increase. However, the increase in plasma volume occurs in a greater proportion compared to the increase in erythrocytes, resulting in a decrease in hemoglobin concentration due to hemodilution. During pregnancy the amount of blood increases. The increase in blood cells is less than the increase in plasma, resulting in blood thinning. The increase was in plasma by 30%, blood cells by 18% and hemoglobin. Anemia during pregnancy is a health problem that is often encountered in pregnant women which can cause complications in future pregnancies. The importance of information about anemia for the community and appropriate methods that can reach the community are important to reduce the risk of maternal death. The aim of this community service is to increase the knowledge of pregnant women by providing health education about preventing anemia. The method used is by providing health education about preventing anemia. As a result of this activity, pregnant women's knowledge about anemia and how to prevent anemia has increased after the outreach activities were carried out.